EVALUASI SISTEM PELAYANAN TERPADU KECAMATAN JAMBI TIMUR MENGGUNAKAN KERANGKA KERJA COBIT 5 PADA DOMAIN DELIVER, SERVICE AND SUPPORT - Hermawan, Redo; Pahlevi, M Riza (LPPM Universitas Dinamika Bangsa, 2019)
Jambi Timur District has implemented a computerized integrated service system in its business process.However, there is no guarantee that the implemented system is said to be good. Therefore, an evaluationis being required to measure the extent of the process in the Jambi Timur District. COBIT 5 is an ITgovernance framework consisting of 37 processes that are loaded into four domains. One of the domainsis Deliver, Service and Support which discusses how IT is implemented., The overall DSS domainassessment has reached level 3 while the expectations of stakeholders in some processes is level 4, whichmeans there is a gap as much as one level. Based on the results of the study, recommendations forimprovements were made to improve IT services and utilization in Jambi Timur District.